Confirming TDP2 mutation in spinocerebellar ataxia autosomal recessive 23 (SCAR23). (August 2018) - Zagnoli-Vieira, Guido; Bruni, Francesco; Thompson, Kyle; He, Langping; Walker, Sarah; de Brouwer, Arjan P.M.; Taylor, Robert; Niyazov, Dmitriy; Caldecott, Keith W.
Abstract : Objective: To address the relationship between mutations in the DNA strand break repair protein tyrosyl DNA phosphodiesterase 2 (TDP2) and spinocerebellar ataxia autosomal recessive 23 (SCAR23) and to characterize the cellular phenotype of primary fibroblasts from this disease. Methods: We have used exome sequencing, Sanger sequencing, gene editing and cell biology, biochemistry, and subcellular mitochondrial analyses for this study. Results: We have identified a patient in the United States with SCAR23 harboring the same homozygous TDP2 mutation as previously reported in 3 Irish siblings (c.425+1G>A). The current and Irish patients share the same disease haplotype, but the current patient lacks a homozygous variant present in the Irish siblings in the closely linked gene ZNF193, eliminating this as a contributor to the disease. The current patient also displays symptoms consistent with mitochondrial dysfunction, although levels of mitochondrial function in patient primary skin fibroblasts are normal. However, we demonstrate an inability in patient primary fibroblasts to rapidly repair topoisomerase-induced DNA double-strand breaks (DSBs) in the nucleus and profound hypersensitivity to this type of DNA damage. Conclusions: These data confirm the TDP2 mutation as causative for SCAR23 and highlight the link between defects in nuclear DNA DSB repair, developmental delay, epilepsy, and ataxia.